Influence of Type and Concentration of Plasticizers on the Properties of Edible Film From Mung Bean Proteins - Wittaya*, Thawien (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Edible film from mung bean proteins (Vigna radiate (L.) Wilczek) were developed based on formulation conditions explored in the previous study. The aim of this study was to investigate the influence of type and concentration of plasticizer on the properties of edible films obtained from mung bean protein. Type and concentration of plasticizer significantly (p<0.05) affected the mechanical and barrier properties of the films. As plasticizer concentration increased, tensile strength decreased concomitant with increase in elongation at break and water vapor permeability. The similar trend behavior was observed for the film solubility and protein solubility, which increased with increasing plasticizer concentration. Sorbitol plasticized films provided the most brittle and tensile strength was the highest (2.40 - 7.23 MPa); however, its effect on water vapor permeability was low (44.38 - 64.48 g.mm/m2.d.kPa). In contrast, polyethylene glycol and glycerol plasticized films exhibited flexible structure, even though, the tensile strength was low (2.39-5.07 and 2.28 - 3.75 MPa, respectively), resulting in increased water vapor permeability (78.38 - 204.19 and 125.16 - 238.20 g.mm/m2.d.kPa). Sorbitol plasticized films, showed higher both film solubility and protein solubility compared to polyethylene glycol and glycerol plasticized films. Mung bean protein films plasticized with sorbitol were yellowish color as indicated by higher b* compared to polyethylene glycol and glycerol plasticized films. It was observed that the films plasticized with sorbitol and polyethylene glycol had lower moisture content than those with glycerol. Keywords: edible films, mung bean proteins, plasticizer, mechanical properties, barrier properties E-mail: thawean.b@psu.ac.th0